2022
DOI: 10.3390/ijms23169284
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of High Mechanical Strength Chitosan/Oxidized Tannic Acid Composite Film with Schiff Base and Hydrogen Bond Crosslinking

Abstract: Chitosan-based composite films with good biodegradability, biocompatibility, and sustainability are extensively employed in the field of food packaging. In this study, novel chitosan/tannic acid (CTA) and chitosan/oxidized tannic acid (COTA) composite films with excellent mechanical and antibacterial properties were prepared using a tape casting method. The results showed that, when 20% tannic acid (TA) was added, the tensile strength of the CTA composite film was 80.7 MPa, which was 89.4% higher than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As mentioned, the synthesis of OTA was synthesized via laccase oxidization to generate quinone in situ by oxidation of accessible tyrosyl grafted phenol units [26]. Such reaction preferentially oxidized the phenolic hydroxyl group of the TA structure to become reactive o-quinones, which was validated in literature [50]. TA as a stabilizer to prepare TA modified AuNPs was also explored [25].…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned, the synthesis of OTA was synthesized via laccase oxidization to generate quinone in situ by oxidation of accessible tyrosyl grafted phenol units [26]. Such reaction preferentially oxidized the phenolic hydroxyl group of the TA structure to become reactive o-quinones, which was validated in literature [50]. TA as a stabilizer to prepare TA modified AuNPs was also explored [25].…”
Section: Discussionmentioning
confidence: 96%
“…The composite films have good hydrophilicity, water absorption, elasticity, biocompatibility, thermal stability, and antibacterial effect. Qin et al [104] prepared CS/tannic acid (CTA) and CS/oxidized tannic acid (COTA) composite membranes by the tape method. The results showed that the composite film had excellent mechanical properties and antibacterial properties, and it had an obvious antibacterial effect on Escherichia coli.…”
Section: Schiff Alkalization Reactionmentioning
confidence: 99%
“…No significant differences in the elongation at break values were observed between the studied samples. Qin et al [61] observed that the addition of tannic acid to chitosan results in an increase in tensile strength as well as the Young Modulus. 0Also, Sun et al [62] documented that the presence of gallic acid results in a significant increase in the tensile strength of the studied chitosan/gallic acid films.…”
Section: Mechanical Propertiesmentioning
confidence: 99%